Interindividual differences in preferred directions of perceptual and motor decisions - Schütz, Alexander C.; Justus Liebig University Giessen (My University, 2014)
Both the perceptual system and the motor system can be faced with ambiguous information and then have to choose between different alternatives. Often these alternatives involve decisions about directions, and anisotropies have been reported for different tasks. Here we measured interindividual differences and temporal stability of directional preferences in eye movement, motion perception, and thumb movement tasks. In all tasks, stimuli were created such that observers had to decide between two opposite directions in each trial and preferences were measured at 12 axes around the circle. There were clear directional preferences in all utilized tasks. The strongest effects were present in tasks that involved motion, like the smooth pursuit eye movement, apparent motion, and structure-from-motion tasks. The weakest effects were present in the saccadic eye movement task. Observers with strong directional preferences in the eye movement tasks showed shorter latency costs for target-conflict trials compared to single-target trials, suggesting that directional preferences might be advantageous for solving the target conflict. Although there were consistent preferences across observers in most of the tasks, there was also considerable variability in preferred directions between observers. The magnitude of preferences and the preferred directions were correlated only between few tasks. While the magnitude of preferences varied substantially over time, the direction of these preferences was stable over several weeks. These results indicate that individually stable directional preferences exist in a range of perceptual and motor tasks.
Keywords: saccadic eye movements; smooth pursuit eye movements; apparent motion; structure-from-motion; hand movements; ddc:150